PIGMEN MERAH DARI JAMUR YANG DIISOLASI DARI TANAH TEMPAT PEMBUANGAN LIMBAH SUSU - Sastrawidana, I D. K.; Maryam, Siti; Sudiana, I Ketut (Jurnal Kimia (Journal of Chemistry); Vol. 9, no. 1 Januari 2015, 2015)
The use of synthetic dyes in enhancing the consumer appeal of the product is increasing, but most synthetic dyes are toxic, carcinogenic and difficult to degrade, causing environmental pollution. The purpose of this study is to analyze the characteristics of the red pigments produced by fungi isolated from soil contaminated with goat milk. Stages of research include semisolid fermentation using PDA and milk as a supporting medium for pigment production. Pigment analysis involves determining the characteristics of the spectrum as well as the stability of the colour upon pH and temperature treatments. The results showed that the spectrum of the red pigment from the fungus consisted of two peaks at 416 and 493 nm, the colour was stable at a temperature range of 40-90 o C and at pH range of 5-8.
Keywords: Pigment, Fungus, Color stability